Naturally Dried Graphene Aerogels with Superelasticity and Tunable Poisson's Ratio. Issue 41 (5th September 2016) - Xu, Xiang; Zhang, Qiangqiang; Yu, Yikang; Chen, Wenli; Hu, Han; Li, Hui
Abstract : A novel natural drying (ND) strategy for low‐cost and simple fabrication of graphene aerogels (GAs) is highlighted. The as‐formed NDGAs exhibit ultralarge reversible compressibility (99%) and tunable Poisson's ratio behaviors (−0.30 < ν < 0.46), which suggests promising applications in soft actuators, soft robots, sensors, deformable electronic devices, drug release, thermal insulator, and protective materials.